2011
DOI: 10.1016/j.resp.2011.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Airway epithelium mediates the anti-inflammatory effects of exercise on asthma

Abstract: Airway epithelium plays an important role in the asthma physiopathology. Aerobic exercise decreases Th2 response in murine models of allergic asthma, but its effects on the structure and activation of airway epithelium in asthma are unknown. BALB/c mice were divided into control, aerobic exercise, ovalbumin-sensitized and ovalbumin-sensitized plus aerobic exercise groups. Ovalbumin sensitization occurred on days 0, 14, 28, 42, and aerosol challenge from day 21 to day 50. Aerobic exercise started on day 22 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
69
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(77 citation statements)
references
References 32 publications
6
69
0
1
Order By: Relevance
“…Vieira et al (19) were the first to demonstrate a reduction or an improvement in each of the following after aerobic exercise in patients with asthma: airway epithelial oxidative and nitrosative stress, Th2 cytokines, chemokines, adhesion molecules, anti-inflammatory effects, growth factors, and matrix metalloproteases. These anti-inflammatory effects of NF-kB and the reduction of purinergic receptor P2X7 are related to the increased epithelial secretion of IL-10.…”
Section: Discussionmentioning
confidence: 99%
“…Vieira et al (19) were the first to demonstrate a reduction or an improvement in each of the following after aerobic exercise in patients with asthma: airway epithelial oxidative and nitrosative stress, Th2 cytokines, chemokines, adhesion molecules, anti-inflammatory effects, growth factors, and matrix metalloproteases. These anti-inflammatory effects of NF-kB and the reduction of purinergic receptor P2X7 are related to the increased epithelial secretion of IL-10.…”
Section: Discussionmentioning
confidence: 99%
“…Regular aerobic exercise performed at low or moderate intensity decreased eosinophilic and lymphocytic inflammation and Th-2 immune response in a murine model of allergic asthma (Pastva et al, 2004;Vieira et al, 2007Vieira et al, , 2008Vieira et al, , 2011Hewitt et al, 2009Hewitt et al, , 2010Lowder et al, 2010). These studies showed that the effects of exercise training were mediated by reduced activation and expression of NF-kB, insulin like growth factor 1 (IGF-1), RANTES (CCL2) and glucocorticoid receptors.…”
Section: Studies In Animal Models and Cultured Bronchial Epithelial Cmentioning
confidence: 90%
“…However, the degree and type of airway inflammation under resting conditions is variable in athletes who perform different sports, and the role of inflammatory cells in the airways is currently unclear. Furthermore, airway inflammation in endurance athletes shows some peculiarities, since it may not be associated with bronchial hyperreactivity, post-exercise respiratory symptoms Bonsignore et al, 2001) or clear evidence of cell activation after acute exercise in humans or mice (Bonsignore 2001(Bonsignore , 2003bMorici et al, 2004;Hewitt et al, 2008) or after training in animal models (Chimenti et al 2007(Chimenti et al , 2009Silva et al, 2010;Vieira et al, 2007Vieira et al, , 2011.…”
Section: Exercise-induced Changes In Airway Cellsmentioning
confidence: 99%
“…In this direction, since 2004 a growing number of experimental studies using mouse models of chronic allergic airway inflammation have demonstrated that low and moderate intensity aerobic exercise performed either before, during or after the allergen sensitization results in decreased eosinophilic inflammation, Th2 cytokines production, airway remodeling and hyperresponsiveness [16][17][18][19][20][21][22][23][24]. Shortly, these studies have demonstrated that these beneficial effects can be attributed to decreased activation of leukocytes and bronchial epithelial cells as a result of increased activation of glucocorticoids receptors, T-regulatory cells resulting in increased synthesis of anti-inflammatory cytokine IL-10, and decreased activation of transcriptional factor NF-kB [16][17][18][19][20][21][22][23][24].…”
mentioning
confidence: 99%
“…Shortly, these studies have demonstrated that these beneficial effects can be attributed to decreased activation of leukocytes and bronchial epithelial cells as a result of increased activation of glucocorticoids receptors, T-regulatory cells resulting in increased synthesis of anti-inflammatory cytokine IL-10, and decreased activation of transcriptional factor NF-kB [16][17][18][19][20][21][22][23][24]. In addition, these studies also demonstrated that aerobic exercise present a direct inhibitory effect on the pulmonary oxidants production as well as on the synthesis of mediators involved in the airway remodeling process [19,24]. However, the precise cellular and molecular mechanisms of beneficial effects of aerobic exercise for asthma deserve further investigations.…”
mentioning
confidence: 99%